Trash Talk Among Mobile Legends Bang-Bang Game Players (A Phenomenological Study On College Students In Pekanbaru) - Ningsih, Rindiani; Asriwandari, Hesti; Marnelly, T. Romi (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Mobile Legends Bang-Bang is one of the most popular games in Indonesia with more than 500 million downloaders on Play store App in 2024. Playing online games is done for entertainment, to have fun, to soothe the mind, to fill free time, and to make new friends. Mobile Legends Bang-Bang players often use trash talk in their interactions. Trash talk can be understood as a communication style that is aggressive, shows disrespect, and creates a competitive atmos-phere. The research uses qualitative method with phenomenological approach. The types and sources of data obtained through primary and secondary data. Data collection techniques are observation, interview, and documentation techniques. The study's findings indicate the causes of trash talk among Mobile Legends Bang-Bang players includes: trash talk towards their teammate, trash talk to the other team, internet connection problem, influenced by other players, and interruption from people during play. Besides that, there are also consequences of trash talk includes: interaction between players after the game ends, players"™ daily lives are affected by trash talk, and player self-reflection after trash talking.